2021
DOI: 10.1016/j.ijid.2021.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of enteric virus infections in children living in the Amazon region

Abstract: To verify the frequency of viruses causing acute gastroenteritis (AGE) in association with the histo-blood group antigen (HBGA) and Rotarix TM vaccination coverage in children from the Amazon region. Design: Fecal and saliva samples were collected from children with AGE (n = 485) and acute respiratory infection (ARI) (n = 249) clinical symptoms. Rotavirus A (RVA), norovirus, human adenovirus (HAdV), and sapovirus (SaV) were verified in feces by molecular detection. Saliva samples were used for HBGA phenotyping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 40 publications
2
21
1
Order By: Relevance
“…In Brazil, some studies performed pre- and post-rotavirus vaccine introduction reported HAdV detection rates ranging from 3.9 to 6.8%, indicating a minor impact of HAdV as an etiologic agent of AGE in Brazil 29 31 . In contrast, but similar to our findings, data from two recent studies conducted in Northern and Southeastern Brazil reported HAdV detection rates of 28.6% and 18.5%, respectively, among children with AGE symptoms 32 , 33 . Another study in Northern Brazil has detected HAdV in 50% of stool samples from hospitalized children with AGE 34 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Brazil, some studies performed pre- and post-rotavirus vaccine introduction reported HAdV detection rates ranging from 3.9 to 6.8%, indicating a minor impact of HAdV as an etiologic agent of AGE in Brazil 29 31 . In contrast, but similar to our findings, data from two recent studies conducted in Northern and Southeastern Brazil reported HAdV detection rates of 28.6% and 18.5%, respectively, among children with AGE symptoms 32 , 33 . Another study in Northern Brazil has detected HAdV in 50% of stool samples from hospitalized children with AGE 34 .…”
Section: Discussionsupporting
confidence: 91%
“…Given these high detection rates along with the exposure to multiple viruses at similar times increase the likelihood of multiple infections within a short window of time in the same host 54 . Co-detections among enteric viruses are commonly reported, and studies from Brazil, Bangladesh, USA and France have demonstrated the co-detection of HAdV with rotavirus and norovirus, but at lower rates 22 , 33 , 55 57 . In addition, Liu et al (2016) 44 detected two or more diarrhoea-associated pathogens in almost 40% of 5304 stool samples tested for 32 enteropathogens in the GEMS case–control study with children under the age of five from countries in Africa and Asia.…”
Section: Discussionmentioning
confidence: 99%
“…High-risk surfaces are not determined by the frequency with which they are touched but by how many individuals touched them. Considering children (younger than 5 years) are the most vulnerable population group because they have low immunity, the strategies on norovirus prevention and control for children should be given more attention ( Olivares et al, 2021 ;Safadi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…94 No association was found between HBGA and susceptibility to SaV infection among children from the Amazon region. 73 Human and at a low frequency in the general population. 95 Individuals with blood group A are found susceptible to HAdV infection which might partially explain the failure to acquire antibodies in childhood due to raised natural resistance.…”
Section: Other Enteric Virusmentioning
confidence: 99%
“…97 There is a limited studies describing the clear association between HBGAs and HAdV infection suggesting that more investigations are needed to understand the role of HBGAs in determining genetic susceptibility or resistance to HAdV infection. 73 6 | ASSOCIATION OF HISTO-BLOOD GROUP ANTIGEN WITH ENTERIC BACTERIA AND SOME GASTROINTESTINAL DISEASES…”
Section: Other Enteric Virusmentioning
confidence: 99%